2012
DOI: 10.1063/1.3686215
|View full text |Cite
|
Sign up to set email alerts
|

Metalized heterogeneous detonation and dense reactive particle flow

Abstract: Abstract. Metalized heterogeneous detonation and subsequent dense reactive particle flow have become a rapidly growing research area. Selected recent developments are reviewed with an emphasis on particle aspects in three parts: detonation-particle interactions, particle reaction and instability of particle dynamics. This includes the breakdown of the CJ detonation, detonation shock interaction effects on wave velocity, critical failure diameter, post-combustion and particle morphology, shocked particle reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…At higher dispersal speeds, the droplet or particle cloud is highly perturbed and coherent jet structures form during the expansion (see Fig. 1) [6][7][8][9][10][11][12][13][14]. The formation of particle clusters and jets is widely observed in nature, with examples such as supernovae, volcanic eruptions, embedded landmine explosions and shallow underwater explosions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At higher dispersal speeds, the droplet or particle cloud is highly perturbed and coherent jet structures form during the expansion (see Fig. 1) [6][7][8][9][10][11][12][13][14]. The formation of particle clusters and jets is widely observed in nature, with examples such as supernovae, volcanic eruptions, embedded landmine explosions and shallow underwater explosions.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental initial particle expansion velocity was found to be related to the so-called "Gurney velocity", which is determined from both the explosion energy and mass ratio of dispersal payload to explosive. Through meso-scale simulations Xu et al [12,13] indicated that micro-jets of detonation products are developed due to the non-uniform density effect at the multiphase interface between the center explosive and the surrounding packed particle bed; this could lead to one of the origins of jetting formation.…”
Section: Introductionmentioning
confidence: 99%
“…The second characteristic is that the combustion will generate solid Al 2 O 3 , which may further influence detonation product expansion. These multi-phase interactions make Al combustion very complicated, resulting in many unresolved problems [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the failure along the wafer edge does not occur uniformly, but instead occurs locally forming discrete particle jets. These jets associated with the failure of the wafer are analogous with the jets that form in large-scale multiphase explosions [3,8]. The spherical expansion of the solid explosives does not generate shear in the surrounding packed particle bed shell, instead the outward radial motion results in a circumferential tension in the particle shell.…”
Section: Downstream Surface Visualizationmentioning
confidence: 99%
“…The shock wave initially propagates through a granular particle bed and much later after the passage of the shock wave, the particles are further dispersed by the radial combustion product flow forming a cloud. In this application it is important to understand the dispersion of the particles as the energy release from the particles maintains the pressure in the shock sphere, thereby increasing the shock wave impulse [3]. The particle dispersion phenomenon varies from early time when the particle volume fraction is large, to later time where the volume fraction is very small and the flow is considered a dilute gas-solid flow, i.e., similar to a dusty-gas flow.…”
Section: Introductionmentioning
confidence: 99%